MEK2 negatively Regulates LPS Mediated IL-1β Production Through HIF-1α Expression - Talwar, Harvinder (J Immunol, 2019)
LPS activated macrophages require metabolic reprogramming and glucose uptake mediated by hypoxia inducible factor (HIF-1) α and glucose transporter (Glut)1 expression for proinflammatory cytokine production, especially IL-1β. This process is tightly regulated through activation of mitogen-activated protein kinases (MAP) kinases including the MEK/ERK pathway as well as several transcription factors including HIF-1α. While Mitogen-Activated Protein Kinase Kinase (MEK) 2 deficiency had no significant effect on nitric oxide, TNF-α, and IL-12 production in response to LPS challenge, MEK2 deficient murine bone marrow derived macrophages (BMDMs) exhibited lower IL-10 production. Importantly, MEK2 deficient BMDMs exhibited a preserved ERK1/2 phosphorylation, higher HIF-1α, Glut1 levels and substantially increased IL-1β as well as IL-6 production in response to LPS stimulation. Knockdown of HIF-1α expression via small interfering RNA (siRNA) decreased the level of HIF-1α expression in MEK2 deficient BMDMs and decreased IL-1β production in response to LPS treatment. Furthermore, we performed gain of function experiments by overexpressing MEK2 protein in RAW264.7 cells. LPS stimulation of MEK2 overexpressed in RAW264.7 cells led to a marked decreased IL-1β production. Finally, we investigated the role of Mek1 and Mek2 double and triple mutation on ERK phosphorylation, HIF-1α expression and IL-1β production. We found that MEK2 is the major kinase, which inversely proportionally regulates HIF-1α and IL-1β expression independent of ERK activation. Our findings demonstrate a novel regulatory function for MEK2 in response to TLR4 activation in IL-1β production through modulating HIF-1α expression.